Reality television - Huff, Richard M (Westport, Conn. : Praeger Publishers, 2006)
Includes information on The Amazing Race, American Idol, The Apprentice, Average Joe, The Bachelor, Big Brother, Dancing with the Stars, Dr. 90210, Extreme Makeover, The Gong Show, Joe Millionaire, Last Comic Standing, The Original Amateur Hour, Queen for a Day, Queer Eye for the Staight Guy, The Real World, Survivor, This Old House, Trading Spaces, Trading Spouses, Cory Clark, Donald Trump, Paul Wernick, etc
Survivor : the start of it all -- Where does this stuff come from? -- Casting : finding the freaks, the geeks, and the stars -- Celebrities sing, dance, and claw their way into reality -- Altered reality : the makeover craze -- All is not what it seems : reversed reality -- This show seems awfully familiar -- Love is in the air -- Singing for fame, fortune, or just attention -- Liars, cheaters, and scandals -- Working for a living -- There is a life after reality -- Real or not, it doesn't matter -- The gift that keeps giving
Includes bibliographical references (p. [181]) and index
Keywords: Reality television programs -- United States